Compensation scheme for victims of deviant behaviour in the workplace in Malaysia - Thurasingam, Ambikai S. (2019)
This study examines the operation of compensation for victims of deviant behavior in the workplace and the nature of existence of deviant behaviour against persons in the workplace. The prevalence of deviant behavior in the workplace has been the source of many interests in the social and legal studies but there is still the need to have workable mechanism to deal with the injustice to the victims of such behavior. This study aims to analyse the adequacy of legal regimes on deviant behaviour against persons in the workplace in view of proposing possible legal redress in the form of compensation scheme over different forms of deviant behaviour against persons in the workplace in Malaysia. In doing so, this study analyzes the legal rules under relevant torts and legislations on workplace deviant behaviour, and also examines the weaknesses of their compensation system, apart from the compensation mechanism under the EIS. This study applies the qualitative research approach using the doctrinal, grounded theory and normative research methods. It is found that tort law is based upon certain important conditions under which a person is permitted for the compensation, if the claims are not based on a contractual obligation. Moreover, the damages can result from the loss of life, property, or health from either financial crisis or from breach of rights. Meanwhile, the existing statutory legislation and provisions governing employer – employee relationship and work related misbehaviour and/or misconduct addresses the legal measures in the form of penalties for the victims. It is evident that these legislations impart provisions that are prohibitive in nature, and did not take cognizance of the compensation available for the injured party(s). Provisions of justice for workplace deviance victims are needed in terms of a reorientation of focus from punishment for the deviance against persons. This study suggests amendments in the existing employment laws to enable the aggrieved victims to claim compensation without the risk of litigation based on the gravity of the deviance.